Mechanical Properties of Powder Injection Molded Ni-Based Superalloys - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2011)
This paper describes the microstructural and mechanical properties of powder injection moulded (PIM) Ni based superalloys. Ni-based superalloys were mixed with a polymeric binder (paraffin wax, carnauba wax, stearic acid and PP) and injection moulded as standard tensile bars. The critical powder loading for injection moulding were 62.5 vol. % for standard samples. Binder removal, debinding, was performed using a two-step solvent/thermal method. After debinding the samples were sintered at 1100 degrees C and at 1285 degrees C under high level vacuum. Metallographic studies were conducted to reveal the extent of densification and the corresponding microstructural changes. Ni 718, Ni 625 and Nimonic90 samples achieved high sintered densities via supersolidus liquid phase sintering. The mechanical properties of Ni 718, Ni 625 and Nimonic90 are determined and compared with the properties of previously reported studies on similar PIM materials.
Keywords: Powder Metallurgy; Powder Injection Moulding; Sintering